2011
DOI: 10.1002/imhj.20303
|View full text |Cite
|
Sign up to set email alerts
|

The mothers and toddlers program, an attachment‐based parenting intervention for substance‐using women: Results at 6‐week follow‐up in a randomized clinical pilot

Abstract: Previously, we reported posttreatment findings from a randomized pilot study testing a new attachment-based parenting intervention for mothers enrolled in substance-use treatment and caring for children ages birth to 3 years (N.E. Suchman, C. DeCoste, N. Castiglioni, T. McMahon, B. Rounsaville, & L. Mayes, 2010). The Mothers and Toddlers Program (MTP) is a 12-session, weekly individual parenting therapy that aims to enhance maternal capacity for reflective functioning and soften harsh and distorted mental repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
186
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(202 citation statements)
references
References 30 publications
7
186
1
Order By: Relevance
“…In a pilot study examining MTP in a small sample of 14 substance-involved mothers of toddlers who ranged in age from 12 to 36 mo, preliminary pre-postcomparisons indicated that MTP was effective in increasing mothers' reflective functioning, sensitivity to child cues, and responses to child distress (12). These mechanisms of change also improved mothers' depressive symptoms, abstinence from drugs, and responsive caregiving to their children's cues as well as their children's clarity of cues immediately posttreatment and at 6-wk follow-up in a sample of 47 substanceinvolved mothers of young children (i.e., ranging in age from birth to 36 mo) who were randomized to MTP or a parent education program (13,70).…”
Section: Attachment-based Parenting Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a pilot study examining MTP in a small sample of 14 substance-involved mothers of toddlers who ranged in age from 12 to 36 mo, preliminary pre-postcomparisons indicated that MTP was effective in increasing mothers' reflective functioning, sensitivity to child cues, and responses to child distress (12). These mechanisms of change also improved mothers' depressive symptoms, abstinence from drugs, and responsive caregiving to their children's cues as well as their children's clarity of cues immediately posttreatment and at 6-wk follow-up in a sample of 47 substanceinvolved mothers of young children (i.e., ranging in age from birth to 36 mo) who were randomized to MTP or a parent education program (13,70).…”
Section: Attachment-based Parenting Interventionsmentioning
confidence: 99%
“…Further, repeated exposure to addictive substances likely reduces parents' dopaminergic response to stress, resulting in vulnerability to negative emotions and extreme distress when caring for distressed children. Such experiences can trigger relapses for parents who are substance-involved (13). Given the powerful nature of the dopaminergic system, interventions meant to change parenting behaviors in substance-involved families will need to be particularly potent.…”
Section: Neurobiology Of Parenting and Substance Usementioning
confidence: 99%
See 1 more Smart Citation
“…MTP is an attachment-based parenting intervention designed to enhance parent-child relationships by improving maternal refl ective functioning and the quality of the mother's mental representations of the child (e.g., being fl exible and balanced as opposed to infl exible and distorted). Researchers at Yale University School of Medicine recently reported the results of a pilot study involving 47 mothers who were enrolled in substance abuse treatment and caring for a child aged birth to 3 years (Suchman et al 2010(Suchman et al , 2011. Mothers were randomly assigned to participate in 12 weekly sessions of MTP or a comparison parenting education intervention.…”
Section: Programs Subject To Recent Randomized Trialsmentioning
confidence: 99%
“…Numerous intervention programmes have been designed to improve parental sensitivity in at-risk dyads, and many of these use video interactions as the primary source of data Marvin, Cooper, Hoffman, & Powell, 2002;McDonough, 2005;Sadler, Slade, & Mayes, 2006;Suchman, Decoste, McMahon, Rounsaville, & Mayes, 2011). The Tuned-InParenting Programme (TIP) is a video-interaction group intervention for parents and infants at a targeted level of intervention (Priddis & Wells, 2010Priddis, Wells, Dore, Booker, & Howieson, 2008).…”
Section: Introductionmentioning
confidence: 98%